HRM and temporary workers' well-being: a study in Portugal and Brazil. Issue 3 (3rd August 2015) - Chambel, Maria José; Farina, Anete
Abstract : Purpose: – Temporary agency workers (TAWs) are regarded as experiencing employment conditions that tend to facilitate high strain. In this study, the authors view this situation as not being inevitable and dependent on the opportunity of having positive experiences in the professional context. The purpose of this paper is to propose that perceptions of the human resource management (HRM) practices system are positively related to work engagement, which in turn, is positively related to context free well-being. Design/methodology/approach: – These hypotheses were tested with two samples of TAWs, from Portugal ( n =241) and Brazil ( n =228), contracted by the same international agency. Data were analyzed with multiple group analyses. Findings: – Results confirmed that in both the Portuguese and Brazilian samples the HRM practices system is positively related to TAWs' context free well-being and their work engagement mediates this relationship. However, the authors also verified that the relationship between work engagement and satisfaction with life was stronger for the Portuguese TAWs than for their Brazilian counterparts. Research limitations/implications: – The study is limited, due to the nature of the data (self-reported) and the lack of a longitudinal design. Practical implications: – An important implication of this research study is that agencies should acknowledge the fact that HRM practices are an investment with a return from TAWs, since they are positively related to their well-being. Originality/value: – The findings highlight the importance of the HRM practices system in developing positive psychological states with TAWs, not only at work, but also outside this context. This observation was confirmed in two different countries.